Correlação entre o peso da palha e o das sementes, em variedades de feijão (`Phaseolus vulgaris L) - Vieira, Clibas; Ribeiro Gomes, Fábio (Revista Ceres, 2025)
Correlation between weight of straw at harvest time (stems, leaves, empty pods, and residual root system) and the weight of dry seeds (sufficiently dried for storage), in 23 field bean varieties, gave a mean coefficient of regression b=0.61. On theaverage anincrease of lkg. in straw weight gave a corresponding increase of 0, 61 kg. in seed weight. There was a significant difference in coefficients of regression between va- rieties (see table 3). In three varieties straw weight and seed weight behaved as independent variables.